Identifikasi Fungsi dan Kriteria Estetika Taman Kota Pasif di Kota Semarang - Harjanti, Intan Muning; Zayyansari, Anita (Badan Riset dan Inovasi Daerah Kota Semarang, 2024)
As population and human activity surge, Green Open Space (RTH) in cities is increasingly being pushed, changing its function to housing and infrastructure. In fact, green open space and city governance play an important role in creating comfortable housing. Urbanparks, as a type of green open space, come in two types: active and passive. In Semarang, the construction of passive urban parks is being promoted. This research identifies the functions and aesthetic criteria of passive urban parks in Semarang. A qualitative descriptive method with triangulation of theory, sources and methods is used to analyze the data. The research results show that passive urban parks in Semarang have aesthetic functions, specifically: beautifying the visual environment and supporting city planning; Increase productivity, creativity and architectural beauty; and displaying regional characteristics through monuments or directional signs. Meanwhile, the aesthetic criteria for passive urban parks in Semarang include: unity and consistency of design elements; balance between garden elements; variations in plant height and color; selection of contrasting plant colors; repetition of elements or patterns; beautiful garden shape; strategic location in the middle of the city, main roads or road islands. It is hoped that these findings can be a guide in developing passive urban parks in Semarang so that they suit their intended purpose and maximize their benefits for the community.